Comparative Study on Lower-Middle-, Upper-Middle-, and Higher-Income Economies of ASEAN for Fiscal and Current Account Deficits: A Panel Econometric Analysis - Maran Marimuthu; Hanana Khan; Romana Bangash (Mathematics, 2022)
For the last three decades, ASEAN has been facing a persistent fiscal deficit. However, the impact of fiscal deficit on the current account deficit in the sub-groups of ASEAN is still unknown. This study aims to investigate the impact of fiscal deficit on current account deficit and their relationship among the three sub-groups of ASEAN which are based on gross national income (GNI), i.e., lower-middle-, upper-middle-, and higher-income countries. The analysis covers the panel data collected over the span of the last three decades (1990–2020) for ten Southeast Asian nations (ASEAN). The analyses incorporate the panel methodology for data analysis such as panel unit root for checking data stationarity, cointegration testing, panel autoregressive distributed lag (PARDL) for short- and long-run analysis, cointegration regression (fully modified and dynamic ordinary least squares) for significance, the panel Dumitrescu and Hurlin Granger causality test for examining causal relationships in tested variables, and stability diagnostics and CUMSUM and CUSUMSQ techniques for structural breaks and coefficient stability in the model. In lower-middle-income economies (LMIE), results indicate the existence of a unidirectional causal relationship from the current account deficit (CAD) to the fiscal deficit (FD), suggesting a reverse causal relationship from CAD to FD. In the long run, FD does not significantly induce CAD, while real interest rate (RIR) and exchange rate (EXC) influence CAD. In upper-middle-income economies (UMIE), results specify that there is no causality between FD and CAD. The RIR, EXC, and FD are significant to CAD in the long run. In higher-income economies (HIE), RIR and FD have an influence on CAD in the long run period. Moreover, from CAD to FD, a unidirectional causal association exists, and likewise for LMIE. This is a reverse causal relationship from CAD to the FD, supporting the current account targeting hypothesis (CATH) in both the LMIE and HIE groups. This study recommends that the LMIE and HIE groups can use the fiscal deficit as a tool to eliminate the unfavorable current account position. Policymakers can target EXC and RIR to stabilize CAD in long run. In UMIE and HIE, policymakers must consider FD alarming, as it can induce CAD in the long run. The RIR can be the targeted factor in the sub-groups of ASEAN.